Instant Messaging for Collaboration: A Case Study of a High‐Tech Firm - Quan‐Haase, Anabel; Cothrel, Joseph; Wellman, Barry (Journal of computer-mediated communication, 2005)
This article examines uses of instant messaging (IM) in a high‐tech firm to illustrate how knowledge workers use this new work tool to collaborate with co‐workers. The objectives are 1) to identify the collaborative practices of individuals in mediated work environments by looking at uses of IM; 2) to discern what social processes are reflected in employees' use of IM; and 3) to investigate how three factors proposed by Erickson and Kellogg (2000) to support social processes—visibility, awareness and accountability—are used in an IM system. Questionnaire and interview data show that while IM leads to higher connectivity and new forms of collaboration, it also creates distance: employees use the mediated environment as a shield, distancing themselves from superiors. We use Erickson & Kellogg's ‘social translucence of technology’ framework to discuss the social consequences of working in a computer‐mediated work environment.